ChatGPT li Ta'allum al-Lughah al-'Arabiyah: Imkanat wa Hudud - Nasaruddin, Nasaruddin; Dimyathi, Muhammad Afifudin; Taufiq, Mirwan Akhmad; Yani, Achmad (Arabi : Journal of Arabic Studies, 2024)
This research examines the possibilities and limitations of using ChatGPT in learning Arabic as a foreign language. Using a descriptive method, this study presents theories regarding using ChatGPT in language learning and how it is practically applied in learning Arabic as a foreign language. It also highlights the limitations learners should consider when using this application correctly and effectively. This research indicates that ChatGPT can assist Arabic language learners as "smart students" and "smart learning partner." With this role, ChatGPT can help them complete tasks and assignments, create a flexible and personalized learning environment, and improve their language skills. However, learners should also be mindful of the limitations of using ChatGPT, especially regarding ethical aspects and the limitations of the technology itself. They should maintain academic ethics and avoid excessive dependence on ChatGPT, which could negatively impact their critical thinking abilities, engagement spirit, and learning motivation.